2009
DOI: 10.1902/jop.2009.090076
|View full text |Cite
|
Sign up to set email alerts
|

Gingival Inflammation and Interleukin‐1 β and Tumor Necrosis Factor‐Alpha Levels in Gingival Crevicular Fluid During the Menstrual Cycle

Abstract: These results demonstrate that the fluctuation of sex steroid hormones impact gingival inflammation during menstruation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(73 citation statements)
references
References 23 publications
3
67
1
2
Order By: Relevance
“…Some studies hypothesized that estrogen therapy may be used in these periodontal pathologies [45]. However, this therapeutic strategy would be not applicable in gingivitis because it is spontaneously reversed after gingival plaque removing and/or menstrual cycle normalization [46]. Conversely, estrogen deficiency is considered a risk factor for periodontitis [19].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies hypothesized that estrogen therapy may be used in these periodontal pathologies [45]. However, this therapeutic strategy would be not applicable in gingivitis because it is spontaneously reversed after gingival plaque removing and/or menstrual cycle normalization [46]. Conversely, estrogen deficiency is considered a risk factor for periodontitis [19].…”
Section: Discussionmentioning
confidence: 99%
“…It could also be argued that hormonal fluctuations, which were not monitored, may have influenced the results [38, 39]. While this is a possibility, the fact that all subjects had a similar systemic response to dental plaque suggests that such a variation was not a major factor in the present study.…”
Section: Discussionmentioning
confidence: 89%
“…Animal studies in mice have reported that subcutaneous infection of P. gingivalis, with the chamber model, increases maternal TNF-a and enhances adverse pregnancy outcomes (Collins et al 1994, Lin et al 2003. In non-pregnant women with low standardized PlI scores, Baser et al (2009) did not observed changes in TNF-a levels in the GCF throughout menstrual cycle stages. In non-pregnant women with low standardized PlI scores, Baser et al (2009) did not observed changes in TNF-a levels in the GCF throughout menstrual cycle stages.…”
Section: Gingival Index Exhaustive Chaid Analysismentioning
confidence: 97%